Pengembangan Comic Book Digital Berbasis Kearifan Lokal Sebagai Media Belajar di Sekolah Dasar - Guntur, Mochamad; Sahronih, Siti; Nur Indah Septia Ningsih; Lusi Umayah (LPPM POLITEKNIK LP3I BANDUNG, 2022)
Learning is currently in the transition period between online and offline learning, namely limited face-to-face learning. Limited face-to-face learning problems make teachers have to innovate in communication and interactive learning. Comic books can change material that is difficult to understand into material that is easy to understand. This happens because one of the characteristics of comics is that they can visualize abstract material into something real. The purpose of this study is to create a comic book based on local wisdom, which is expected to foster a culture of student literacy by providing alternative media based on applications in the learning process. This study uses the Research and Development (R&D) method, while the model used in this development is the model of ADDIE (Analysis, Desain, Development, Implementation, and Evaluation’). The results of this study obtained very good validation with an average percentage score of 86,03% in terms of material and media design. Also, getting an average score of 96,63% for the percentage of achievement that was tested by users, namely elementary school students, means that students' responses to comics are very good.